Die hedendaagse westerse kultuur* - Merwe, Willie van der (Koers, 1989)
Contemporary Western culture. In dealing with problems besetting contemporary Western culture, the author looks at certain developments. The article deals, in the first place, with a brief overview of the development of Western culture, from the era of the Corpus Christianum to the cultural process which led to the disintegration of the Corpus, viz. the process of secularization. Against the background of this process, there is a focus on two aspects of secularization of great importance for this paper, viz. Man and history and science and technology. The situation is seen to be one hovering between presumption or arrogance and impotence, a sense of anguish inculcated by unbridled development of technology. This sense of angst has caused man to react in certain characteristic ways, and two of these, viz. horizontalism/mysticism and utilirarianism/social romanticism, are discussed. A final similar contrasting pair which can be linked to the polarities of arrogance and impotence would be revolutionary activism and inner emigration. The final point to be made is whether one has to think in terms of judging this inherent opposition in contemporary cultural thought - and what challenge is offered to the church in disseminating the traditional news within a contemporary cultural context.